2014
DOI: 10.1113/expphysiol.2013.071951
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signalling: from discovery to current developments

Abstract: New FindingsWhat is the topic of this review?This is a personal historical review about the discovery and the main conceptual advances leading to our current understanding of purinergic signalling. The contributions of leading figures in the field are acknowledged. It includes the discovery of purinergic neuromuscular and synaptic transmission, cotransmission, the identification of P1 (adenosine), P2X nucleotide ion channel and P2Y nucleotide G protein-coupled receptors, the identity of ectonucleotidases and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
210
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(214 citation statements)
references
References 99 publications
(132 reference statements)
1
210
0
3
Order By: Relevance
“…Suramin also has a number of peripheral effects on innate immunity, metabolism, pain, gut, autonomic, inflammatory, and other pathways regulated by purinergic signaling that may contribute to the beneficial effects observed 8, 23. Previous studies have shown that suramin is taken up into the CNS at the level of the brainstem, although not appreciably into the cerebrum or cerebellum 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suramin also has a number of peripheral effects on innate immunity, metabolism, pain, gut, autonomic, inflammatory, and other pathways regulated by purinergic signaling that may contribute to the beneficial effects observed 8, 23. Previous studies have shown that suramin is taken up into the CNS at the level of the brainstem, although not appreciably into the cerebrum or cerebellum 13.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the cell, extracellular ATP (eATP) is a multifunctional signaling molecule, a potent immune modulator,21 and a damage‐associated molecular pattern (DAMP) that can activate microglia, and trigger IL‐1β production and inflammasome assembly 22. Extracellular purines like ATP, ADP, and adenosine, and pyrimidines like UTP are ligands for 19 different purinergic (P2X, P2Y, and P1) receptors 23. The intracellular concentration of ATP (iATP) in mammalian cells is typically 1–5 mmol/L,24 but drops when ATP is released through membrane channels under stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sympathetic ganglia and their postsynaptic nerves release adenine triphosphate (ATP) [11][12][13][14][15]. Extracellular ATP can activate P2 receptors [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular ATP can activate P2 receptors [14,16]. P2 receptors are divided into P2X and P2Y receptors.…”
Section: Introductionmentioning
confidence: 99%